Are we there yet? - Santat, Dan 1975- (Little, Brown and Company, 2016)
"A boy goes on a long car ride to visit his grandmother and discovers time moves faster or slower depending on how bored he is"--
Keywords: Space and time / Fiction; Automobile driving / Fiction; Space and time / Juvenile fiction; Automobile driving / Juvenile fiction; Picture books for children; Automobile driving; Space and time; Automobile travel / Fiction; Bilderbuch